Melatonin Is a Promising Silage Additive: Evidence From Microbiota and Metabolites - Li, Mao; Lv, Renlong; Zhang, Lidong; Zi, Xuejuan; Zhou, Hanlin; Tang, Jun (Frontiers in Microbiology, 2021)
The safe and effective storage of forage are very important. As an important storage method, ensiling can keep fresh forage for a long time with less nutritional loss. The influence of melatonin on silage microbial or fermentation quality has not been clarified. In the present study, we aimed to clarify whether melatonin affected silage quality via microbiota and metabolites using a stylo (Stylosanthes guianensis) model. Melatonin addition significantly improved the silage fermentation quality, including the increased contents of lactic acid and total acid, as well as the decreased in pH and butyric acid content. Moreover, 16S rRNA sequencing indicated that melatonin addition enhanced the silage microbial diversity indices (such as increase in Shannon indices but decrease in Simpson indices), and significantly shaped the composition of silage microbiota (such as increased abundances of Pantoea, Stenotrophomonas, Sphingobacterium and Pseudomonas, and decreased abundance of Weissella). Melatonin addition also dramatically affected the metabolism of silage microbiota, such as amino acid metabolism, nucleic acid metabolism, carbon metabolism, ABC transporters and so on. Collectively, our results confirmed that the lowest melatonin addition (5 mg/kg) could improved the fermentation quality, and the potential mechanisms might be associated with the microbiota and metabolites in stylo.